Impact of The Existence of A Coffee Store on Family Economic Education and Interest in Entrepreneurship(Case Study in Sudimoro Malang Region ) - Ardy Dwi Wijayanto; Agung Haryono; Heny Kusdiyanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The number of coffee shops in the Sudimoro area makes the Sudimoro area one of the centers for coffee shops in the city of Malang. Based on initial observations, it is known that the existence of a coffee shop in the Sudimoro area has an influence on the family's economic education and interest in entrepreneurship in the community around Sudimoro. This research uses a qualitative approach with the type of case study research. Data collection techniques in this study using observation and interviews. Techniques in data analysis are data collection, data reduction, data presentation, and data inference. The results of the study of the impact of the existence of coffee shops in the Sudimoro area of Malang on family economic education, namely parents familiarize children with saving, teach productive behavior, see future opportunities, be open about family financial conditions and involve family members in family financial planning, and get used to having In addition, the existence of a coffee shop in the Sudimoro Malang area has an impact on interest in entrepreneurship, namely families in the Sudimoro Malang area know knowledge about entrepreneurship, have an interest in entrepreneurship, have the intention and motivation in entrepreneurship.